PERAN JOB QUALITY DAN PEMBERDAYAAN PSIKOLOGIS TERHADAP INOVASI DI PERUSAHAAN START-UP INDONESIA - Hardja, Stella; Widyarini, Maria; Sunardi, Oki (FIA UB, 2020)
Job satisfaction and job quality refer to the achievement level of employee wellbeing and organizational performance. Job quality and psychological empowerment encourage innovation within many business organizations. Previous studies argue that job quality and psychological empowerment are related only to job satisfaction, not innovation especially in service industries and public sector. Thus, this study conceptualized how job quality and psychological empowerment contribute to innovation. As a basis for conceptualization in term of job quality, psychological empowerment, and innovation, this study employed a case study on Indonesian digital startup companies. The conceptual framework performs as the basis for developing further studies.